Testing, testing, one, two, three: Service user evaluation of three standard measures of mental health and well‐being in an online counselling and support service for children and young people. Issue 3 (30th November 2020) - Sefi, Aaron; Frampton, Ian
Abstract: Assessment measures have been widely adopted into mental health settings incorporating idiographic (personalised) and nomothetic (standardised) approaches. Online mental health support services have developed significantly, but with very little testing of these measures. This study assesses the relative merits of acceptability, applicability and appropriateness of assessment measures online for children and young people. Acceptability was determined by whether users elected to complete the measure, applicability by whether they understood the questions, and appropriateness by their experience of completing the measure. Three measures, the Short Warwick‐Edinburgh Emotional and Mental Well‐Being Scale (SWEMWBS), the Young Person's Clinical Outcomes in Routine Evaluation (YP‐CORE) and the Strengths and Difficulties Questionnaire (SDQ), were randomly offered to 7, 235 new registrations to assess relative acceptability of the measures, and two follow‐up questions were asked to assess applicability and appropriateness. The chi‐square tests of independence were calculated to compare response rates for each measure, followed by post hoc pairwise comparisons and effect size calculations. There was a high level of acceptability of the measures, with statistically significant differences between the less‐accepted SDQ and more‐accepted SWEMWBS. For applicability, the SWEMWBS was less understood and relatable than the other assessment measures. All the measures demonstrated a tolerable appropriateness. All differences were indicated at a small effect size. These findings support the acceptability, applicability and appropriateness of the use of assessment measures in an online setting. The SWEMWBS demonstrated surprisingly low applicability against the more clinical measures, suggesting further investigation into how young people ascribe meaning to the measures, and their motivations for completing them.